GASTROPOD COMMUNITY STRUCTURE IN THE INTERTIDAL ZONE OF PASUMPAHAN ISLAND, PADANG CITY, WEST SUMATRA PROVINCE - Oriza, Syucitra; Tanjung, Afrizal; Elizal, Elizal (Asian Journal of Aquatic Sciences, 2023)
Pasumpahan Island is one of the islands located in West Sumatra Province which has various activities of daily life, especially in the intertidal zone; it is suspected that it can interfere with the existence of aquatic organisms one of which is gastropods. Studying the structure of gastropod communities in the intertidal zone is an interesting natural laboratory to study. This research was conducted from December 2021 to January 2022 on Pasumpahan Island Padang City West Sumatra Province. The purpose of this study was to determine the structure of the gastropod community which includes species, abundance, diversity, uniformity, dominance, and distribution pattern of gastropods. As supporting data in this study, several environmental parameters were also measured which included water quality, sediment type, and sediment organic matter content. The research method used is a survey method, where sampling using the quadrat transect method is carried out at 3 stations. Based on the results of the study found 13 species of gastropods. The most common species found at all stations was Pythia scarabaeus, where the gastropod abundance values obtained between stations ranged from 2,78 to 5,00 ind/m2. The value of the species diversity index ranged from 1,50 to 2,02, which was moderate, the uniformity index value ranged from 0,77 to 0,88, which was high uniformity, and the dominance index value ranged from 0,16 to 0,29, meaning that there were no species found dominates and the value of the distribution pattern ranges from 1,31 to 2,47 with a clustered distribution pattern.